Effects of age on spiritual well-being and homonegativity: religious identity and practices among LGB persons in Portugal - Moleiro, C.; Pinto, N; Freire, J (Journal of Religion, Spirituality and Aging, 2013)
The present study explored the effects of age on spiritual well-being and internalized homonegativity among Portuguese lesbian, gay, and bisexual (LGB) persons. A set of questionnaires were filled out by 471 LGB participants using the Lesbian, Gay, and Bisexual Identity Scale; the Spiritual Well-being Scale; and the Multidimensional Measurement of Religiousness and Spirituality. While most participants had been raised Catholic, only 17% currently belonged to a religious denomination. Participants higher in religious well-being were more likely to have concerns in concealing their sexual identity. Existential well-being was related to higher identity affirmation. Older participants reported better spiritual well-being and lower homonegativity.